Answer:
![(x-2)^2=7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nodvvhf1jwcexn39fk63o0xggjor98pnrk.png)
Explanation:
We have been given an equation
. We are asked to complete the square for the given equation.
We know that when an equation is in form
, then we will add
to both sides of equation to make a perfect square.
Dividing both sides by 3, we will get:
![x^2-4x=3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xnumbnkvo0y7m5p6i6hwl478mchd80jc61.png)
Add
on both sides of equation:
![((b)/(2))^2=((4)/(2))^2=2^2=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/u7lb2iwfsaf47squ2vpspxdj52szodb86e.png)
![x^2-4x+4=3+4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/w3gg86jshlxu67ewy0fs6neqar2an66w4c.png)
![x^2-4x+4=7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ry38do2gwsebbr6s8nzkx8gkno47pnc9ge.png)
Now, apply perfect square formula
:
![(x-2)^2=7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nodvvhf1jwcexn39fk63o0xggjor98pnrk.png)
Therefore, our required equation would be
.